LOKALITAS ILMU TAJWID DALAM RISALAH MIFTAH AL-LISAN KARYA K.H. ABDUL DJAMIL NAWAWI - Fiqih Kurniawan (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2019)
Historically, the practice of reading the Qur'an had already existed as Islam entered the archipelago. Unfortunately, the tendency of Qurâ€™anic studies has long been dominated by the tafsir and translation of Qurâ€™an. In the 20th century, the studies of the Qurâ€™an came through a different tendency, namely Tajweed. This paper intends to examnine a treatise of â€œMiftahÂ al-Lisanâ€ written by K.H. Abdul Djamil Nawawi. This treatise is the science of Tajweed that departs from a social phenomenon, namely the community of Quranic tadarus. The media to deliver this treatise are local languages. The other characteristic of â€œMiftahÂ al-Lisanâ€ is that it does not only explain Tajweed, but it also contains laws, verbal solutions, and advice for students and teachers.